The Important in Understanding the Theory of the Firm in the Social Science Research - Alsoaery, Abdulrhman (Advances in Social Sciences Research Journal, 2023)
This article represent the important in understanding the theory of the firm in the social science research. Social science is the scientific study of how people relate within the human society and seek to establish the manner in which people behave. The main theories of the firms are been represented here with it philosophical foundation and an illustration of the interaction of people and organization and how the operation and process can be explained. This article establishes that firm theories are essential for explaining human activities in organization and thereby, it is vital for emerging theories of the firm to have a philosophical foundation.